Mercury(II) and thallium(III) organometallic derivatives of 2-Mercaptobenzoxazole - Castaño, M. V.; Calvo, H.; Sánchez, A.; Casas, J. S.; Sordo, J.; Mascarenhas, Y. P.; Santos, C.de O.P. [UNESP] (Elsevier, 1991)
Some derivatives of 2-mercaptobenzoxazole (HL) of the type MRnL [M = Hg or Tl, R = Me or Ph and n = 1 (Hg) or 2 (Tl)] have been prepared. The structure of HgMeL has been determined by an X-ray diffraction study; in the crystal there are two independent planar molecules in each asymmetric unit, with the ligand in its thiolic form and an almost linear CHgS linkage. Weak intramolecular and intermolecular secondary interactions complement the mercurysulphur bond. The spectroscopic (IR, Raman, mass, 13C-NMR), conductimetric, and dipolar properties of this and the other compounds are discussed. © 1991.